Breaking the Gender Gap: A Two-part Observational Study of the Gender Disparity Among Korean Academic Emergency Physicians - Lee, Mi Jin (J Prev Med Public Health, 2020)
OBJECTIVES: Despite greater access to training positions and the presence of more women in emergency medicine, it has remained a men-dominated field. This study aims to identify the key issues causing the gender gap in Korea and establish measures to overcome them. METHODS: Using the annual statistical reports of the National Emergency Medical Center and data published on the Korean Society of Emergency Medicine website, cases that listed the current status and positions of members in its organization and its committees were analyzed. Secondary analysis was conducted using data from the 2015 Korean Society of Emergency Survey that included physicians’ demographics, academic ranking, years of experience, clinical work hours, training and board certification, core faculty status, position, and salaries. RESULTS: As of September 2019, women account for only 12.7% of the total number of emergency physicians (EP) in Korea; of 119 chair/vice‐chair academic positions, women represented only 9.2%. Women EP were more often assistant professors and fellowship-trained, with fewer in core faculty. However, they worked the same numbers of clinical hours as their men counterparts. The median annual salary of women EP was less than that of men EP after adjusting for academic hospital rank, clinical hours, and core faculty status. CONCLUSIONS: A gender gap still exists among Korean EP, and women earn less than men regardless of their rank, clinical hours, or training. Future studies should evaluate more data and develop system-wide practices to eliminate gender disparities.